Sealants in construction - Klosowski, Jerome M. (Civil engineering, 1989)
This comprehensive treatment of the subject assesses the performance characteristics needed for application plus the preformance properties of generic sealants. Illustrated with 100 photos as well as diagrams which explain fundamentals and outline methods to insure the use of appropriate procedures.